2022
DOI: 10.26877/jp2f.v13i1.11389
|View full text |Cite
|
Sign up to set email alerts
|

Uji Kelayakan E-LKPD Berbasis Problem Based Learning (PBL) Untuk Meningkatkan Keterampilan Proses Sains Siswa SMP

Abstract: Penelitian ini bertujuan untuk mendeskripsikan kevalidan, kepraktisan, dan keefektifan E-LKPD berbasis PBL untuk meningkatkan keterampilan proses sains siswa SMP. Penelitian pengembangan ini menggunakan model ADDIE yang meliputi 5 langkah yaitu (1) Analyze, (2) Design, (3) Develop, (4) Implement, (5) Evaluate. Instrumen penelitian berupa lembar validasi, lembar observasi keterlaksaan pembelajaran, tes, dan angket respon siswa. Penilaian validitas diperoleh dari lembar validasi untuk mengetahui kevalidan E-LKPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…Directly students do not communicate learning with the teacher, that is, many students are embarrassed to ask questions during learning. In line with that, research conducted by Safitri et al, (2022) showed low science process skills caused by the use of worksheets that did not support learning. This statement is reinforced by Sari et al, (2020) which states that the LKPD used in schools has not prepared student KPS because it only contains a few questions that students work on.…”
Section: ▪ Introductionmentioning
confidence: 68%
“…Directly students do not communicate learning with the teacher, that is, many students are embarrassed to ask questions during learning. In line with that, research conducted by Safitri et al, (2022) showed low science process skills caused by the use of worksheets that did not support learning. This statement is reinforced by Sari et al, (2020) which states that the LKPD used in schools has not prepared student KPS because it only contains a few questions that students work on.…”
Section: ▪ Introductionmentioning
confidence: 68%
“…The validation instrument used in this study was adapted from the previous research validation sheet for science worksheets. According to Safitri et al, (2022), a valid category for a science worksheet is one that meets the criteria for format, content, and language.…”
Section: Developmentioning
confidence: 99%
“…In other words, enhancing individual abilities is very important, especially in today's 21st-century learning. Science learning is a process of helping students understand all science concepts (Safitri et al, 2022). Science learning necessitates that students understand the fundamental concepts of science so that they can apply them in their daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature on the subject revealed that it was seen that many experimental researches (Deveci, 2002;Arıcı, 2021;Çanakçı, 2021;Dita et al, 2021;Foo et al, 2021;Ghani et al, 2021;Hasanah et al, 2021;Lestari et al, 2021;Ilma et al, 2021;Putri and Sundayana, 2021;Sari et al, 2021;Shofwani and Rochmah, 2021;Simanjuntak et al, 2021;Suparman et al, 2021;Fong et al, 2022;Kim et al, 2022;Putri et al, 2022;Safitri et al, 2022;Tanrıkulu, 2022;Trullas et al, 2022) were conducted on PBL. It was determined that the researches in the literature focused on determining the effectiveness of PBL in different subjects and comparing it with various learning approaches.…”
Section: Introductionmentioning
confidence: 99%